The Frequency Effect on the Acquisition of –ING Form Structure by Indonesia L2 Learners - Muhammad Fahruddin Aziz; Pratomo Widodo (Journal of English Language Teaching and Linguistics, 2018)
Even though –ing form is acquired earlier based on the natural order hypotheses of L2 morpheme acquisition, it remains difficult for L2 learners to acquire mainly for those who are not frequently exposed to the targeted linguistic feature inputs. A number of investigations were already carried out to find out the frequency effect on the acquisition of verbs as a complement (gerund and infinitive), yet this paper was designed to identify the role of frequency on the acquisition of English –ing form structure by Indonesia L2 learners. Participants consisted of four groups from different semester (1,3,5, and 7). Each semester also indicated various language exposure experienced by L2 learners. Each group comprised 10 participants. Data were collected by employing the writing test to elicit –ing form production including interview and observation. The coding of students’ composition was carried out to determine the correct productions—which were scored to interpret frequency effect on students’ acquisition and their misconceptions in composing a sentence containing –ing forms. The findings revealed that the rate of frequency inputs of –ing form structure accessed by learners fairly contributed to students’ constructional schemas in accordance with the high score. Each word possessed various frequency inputs of distribution which then led them to any deviant production.  In addition, intra-lingual errors were responsible for any misconception perceived by learners (overgeneralization, ignorance of rule restriction, and false concepts hypothesized).